43.3k views
1 vote
The function f and g are defined by: f(x)=3x-2. g(x)=2x+5. Evaluate: 1. g(-6) 2. fg(3)

User Mrimsh
by
6.0k points

1 Answer

4 votes

Answer:

1. -7

2. 31

Explanation:

Given f(x) = 3x - 2 and g(x) = 2x + 5, when given the function with the value of 'x', we can substitute in this value and solve for the function.

1. g(-6) means x = -6 so: g(-6) = 2(-6) + 5 = -12 +5 = -7

2. f(g(3)) means x = 3 in g(x) and that answer will be used for the value of 'x' in f(x). So, start with g(3) = 2(3) + 5 = 6 + 5 = 11, now use x = 11 for f(x): f(11) = 3(11) - 2 = 33 -2 = 31

User Kasun Indrasiri
by
6.6k points